Perancangan Manajemen User Hotspot Server Menggunakan Mikrotik Router di SMAN 1 Lareh Sago Halaban - Rahmi, Kurnia; Musril, Hari Antoni; Supriadi, Supriadi; Okra, Riri (Indonesian Research Journal on Education, 2022)
The purpose of this study is to design a user hotspot server management using Mikrotik at SMA N 1 Lareh Sago Halaban. Based on the results of interviews with ICT BK teachers at SMA N 1 Lareh Sago Halaban that internet access in schools is not yet stable and good network management and hotspot logins have not been regulated. This study uses the Research and Development (R&D) research method with the PPDIOO development model (Prepare, Plan, Design, Implement, Operate, Optimize). The product test used in this research is the validity test, practicality test and effectiveness test. The results of the Quality of Service (QoS) test that the author conducted obtained a delay index of 4 with a very good category, packet loss index 4 with a very good category, throughput index 2 with a sufficient category and a total average of 3.3 with a good category. The results of the product test that the author conducted obtained a validity test from 3 experts, a score of 0.86 was obtained in the valid category, the practicality test from 6 practitioners obtained a value of 0.88 in the practical category and the effectiveness test from 9 appraisers obtained a value of 0.72 in the effective category.